Prosesi Perkawinan Adat Istiadat Lampung Pepadun: sebagai Bentuk Pelestarian Bahasa Lampung - NFN Roveneldo (Badan Pengembangan dan Pembinaan Bahasa, 2017)
The existence of Lampung culture is very important to regard because the culture is a good culture strategy to maintain and develop Lampung language, that is by seeing and examining how the government apply the rules designed by the local government to retain one characteristic in the area, such as language and culture. This study is also conducted to find out how the development of Lampung language and the culture in Lampung province. The results in this study shows that language and culture is slowly eroded by the progression of time. Unfortunately, the education of Lampung language shows a lot of inequality in the learning process. This study uses a qualitative method to look at the use of language Lampung in customs procession that have lasted all this time. Afterwards, the researcher also look at and examine how the role of the government related to Lampung language and its culture,s including the teaching of Lampung language. AbstrakKeberadaan kebudayaan Lampung sangat penting untuk diperhatikan sebab kebudayaan tersebut adalah stategi kebudayaan yang sangat baik untuk memelihara, membina bahasa Lampung. Melihat dan meneliti bagaimana pemerintah mengaplikasikan Peraturan-peraturan yang di rancang oleh pemerintah daerah untuk mempertahankan salah satu ciri khas yang ada di daerah seperti bahasa dan kebudayaan. Penelitian ini juga untuk mengetahui bagaimana perkembangan bahasa lampung dan kebudayaan yang ada di Provinsi Lampung. Hasil dalam penelitian ini bahwa bahasa dan kebudayaan perlahan-lahan terkikis oleh perkembangan waktu. Sungguh disayangkan kependidikan bahasa Lampung banyak ketimpangan dalam proses pembelajaran. Penelitian ini mengunakan metode kualitatif dengan melihat pengunaan bahasa Lampung dalam acara prosesi adat istiadat yang telah berlangsung selama ini. Kemudian melihat dan meneliti bagaimana peran pemerintah terkait bahasa daerah Lampung dan budaya di lihat juga dalam pengajaran bahasa Lampung.